2022
DOI: 10.3389/fenvs.2022.950453
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Trading Non-Green Products and Environment: Introducing Non-Green Trade Openness Index

Abstract: Trade is a significant parameter that may impact environment positively or negatively. However, there is no consensus on this issue among the researchers. It seems likely that tradable products will affect the environmental quality level. However, this requires the separation of the international trade basket. Thus, this research asks whether trade in non-green products affects the level of environmental degradation in the 25 European Union (EU) member states? To answer this question, we develop an index of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…The review of extant literature on trade and environment clearly shows that the focus of past studies has been on overall trade patterns, no effort has so far been made to specifically investigate the environmental impact of the green trade component. Can et al (2022), in a panel study of 25 European Union member countries, find evidence in support of the pollution haven hypothesis. On the basis of the study findings, they claim that non‐green trade openness lowers pollution.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The review of extant literature on trade and environment clearly shows that the focus of past studies has been on overall trade patterns, no effort has so far been made to specifically investigate the environmental impact of the green trade component. Can et al (2022), in a panel study of 25 European Union member countries, find evidence in support of the pollution haven hypothesis. On the basis of the study findings, they claim that non‐green trade openness lowers pollution.…”
Section: Literature Reviewmentioning
confidence: 94%
“…There are several explanations for this association. Production of non-green commodities frequently requires large quantities of energy, mostly from fossil fuels [48] in the BRICS nations. This dependence on fossil fuels hinders the switch to renewable energy sources by increasing greenhouse gas emissions and environmental damage.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change can be described as one of the most pressing challenges of our time [1,2]. Undeniably, global warming is caused by human activities, and climate scientists stress the urgency for immediate action [3].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of global warming include extreme weather events, the melting of glaciers resulting in rising sea levels, and major risks to biodiversity, key infrastructure, and food availability [4]. International trade is one of the human activities that has a major impact on the environment: it causes 20% of global carbon emissions [1]. Xu et al [5] confirmed that, on average, 20-30% of global greenhouse gas (GHG) emissions are created by producing and transporting goods and services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation